#### Solve simultaneous linear equations:

(i) b(c -d)^{2} + a(d – c) + 3c – 3

(ii) x^{3} – x^{2} – xy + x + y – 1

**Solution:**

(i) b(c -d)^{2} + a(d – c) + 3c – 3d

Above terms can be written as,

b(c – d)^{2} – a(c – d) + 3c – 3d

b(c – d)^{2} – a(c – d) + 3(c – d)

Take out common in both terms,

(c – d) [b(c – d) – a + 3]

(c – d) (bc – bd – a + 3)

(ii) x^{3} – x^{2} – xy + x + y – 1

x^{3} – x^{2} – xy + x + y – 1

Rearrange the above terms we get,

x^{3} – x^{2} – xy + y + x – 1

Take out common in both terms,

x^{2}(x – 1) – y(x – 1) + 1(x – 1)

(x – 1) (x^{2} – y + 1)

**More Solutions:**

- Solve the following systems of simultaneous linear equations.
- Solve the following pairs of linear equations.
- Solve simultaneous linear equations: (i) 2/x + 2/3y = 1/6
- Solve simultaneous linear equations: (i) (7x – 2y)/ xy = 5
- Solve simultaneous linear equations: (i) 3x + 14y = 5xy
- Solve simultaneous linear equations: (i) 20/ (x + 1) + 4/ (y – 1) = 5
- Solve simultaneous linear equations: (i) 1/ 2(2x + 3y) + 12/ 7(3x – 2y) = ½
- If r = 3, y =k is a solution of the equation 3x – 4y +7 = 0
- If x = a, y = b is the solution of the equations x -y = 2 and x + y = 4.